Electrical performance of textured stainless steel under fretting. (June 2017) - Esteves, M.; Ramalho, A.; Ramos, F.
Abstract: Sliding between two couplings is the most common situation caused by dynamic solicitations, especially fretting. Preliminary studies suggest the relevance of contact compliance as well as the debris removable and agglomeration affinities. The present work aims to analyse surface texturing influence, on the friction and electric conduction of AISI 304/301 stainless steel subjected to reciprocating fretting tests. Textured surfaces present, most of the times, an increase in life expectancy of the electric connection. The ability to accommodate oxidize wear debris depends on the available open texture (hollow) volume and couplings contact size. Highlights: The influence of texturing in stainless steel was studied. It stands out immediately the ability of any textured surface delaying the increase of resistance. There are clear beneficial effects achieved with both positive (dimples) and negative (hollows). Denser dimple textures tend to maintain lower impedance for a higher amount of time.